PERBANDINGAN DAMPAK KENAIKAN BIAYA ADMINISTRASI SHOPEE DAN TOKOPEDIA DITINJAU DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Dwi March Trisnawaty; Sri Herianingrum (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Advances in technology and information in recent years have significantly influenced trading activities. Many sellers have shifted from conventional physical stores to online platforms, relying primarily on smartphone based transactions. Online marketplaces offer various conveniences that facilitate selling activities; however, these benefits are accompanied by increasing challenges for sellers. Intense competition among marketplaces has resulted in similar features being offered, while differences in administrative policies, particularly fees, have created additional burdens for sellers. Major platforms such as Shopee and Tokopedia play a dominant role in Indonesia’s online shopping ecosystem, making their administrative fee policies especially impactful. This study aims to compare administrative costs imposed by Indonesia’s two largest marketplaces, Shopee and Tokopedia, from the perspective of Islamic business ethics. The research employs a qualitative approach, utilizing literature reviews and data obtained from official websites and other credible online sources. The findings indicate that administrative fees in these marketplaces have increased over time. From the standpoint of Islamic business ethics, such increases may conflict with contractual principles, as they can involve elements of gharar (uncertainty) and injustice toward sellers. Sellers may experience losses due to unilateral fee increases without prior agreement, which often compels them to raise selling prices in order to maintain profit margins.